ACINETOBACTER SPP. AS HEALTHCARE-ASSOCIATED PATHOGENS: EPIDEMIOLOGICAL FEATURES - MARIA A. Shmakova (Фундаментальная и клиническая медицина, 2019)
The genus Acinetobacter is a major cause of severe healthcare-associated infections. Acinetobacter baumannii is one of the six most hazardous multidrug-resistant bacteria in the hospitals world-wide. This review is focused on the epidemiology, microbiological features, ecology, infection control precautions, and preventive measures.